Epidemiological Profile of Asymptomatic Bacteriuria in Pregnant Women at the Mother and Child University Hospital Center of N’djamena: Associated Risk Factors and Antibiotic Resistance (London Journal of Research In Science: Natural and Formal, 2024)
Asymptomatic bacteriuria in pregnant women is a bacterial urinary tract infection without any of the typical symptoms that are associated with a urinary tract infection whose urine culture meets the criteria for urinary tract infection corresponding to a colony count greater than 100 x 106 forming units of bacteria per liter.The objective of this work was to determine the prevalence of asymptomatic bacteriuria in pregnant women and to evaluate the effectiveness of antibiotics against isolated bacteria to better care for pregnant women.
Keywords: MHD; Free convective; Inclination; Poiseuille flow; Runge-Kutta method.; Climate Change; social crisis; collapse; Asymptomatic bacteriuria; pregnant woman; antibiotic resistance; risk factor